مدى اسهام مديري مدارس التعليم الأساسي في اكتشاف ورعاية الطلبة الموهوبين في مدينة المكلا- الجمهورية اليمنية = The Contribution of the principles of basic education schools in identifying and caring for the gifted students in Mukalla City-Republic of Yemen - Al-Hidabi, Dawood Abdulmalek Yahya (University of Science & Technology (USTY),Yemen, 2016)
This research aimed at investigating The contribution of the basic schools principals in identifying and caring for the gifted students in Mukalla city. The researcher used the quantitative and qualitative approach to achieve the aims of the research, and used two tools; the first tool is the questionnaire which was prepared by the researcher, The second one is the open ended interview. The researcher took all the members of the research community who are the principals of the basic schools in Mukalla city. In the open ended interview, the researcher selected two schools, one is governmental and the second is private. The open ended interviews were conducted with group of teachers, students, and two principals, the results are as follows: The knowledge of the characteristics of gifted students and The knowledge of methods of identifying and caring for the gifted students by the principals of basic schools in Mukalla city was high. The contribution of the basic schools principals in Mukalla city in identifying and in caring for the gifted students was average. The administrative and financial obstacles which face the principals of basic schools in Mukalla city in identifying and caring for the gifted students were high. The results of quantitative research part showed that there were no differences in the significance level (α ≤ 0.05) in the responses of a search community whether the school is ( governmental , private ) in identifying and caring for the gifted students. While the results of qualitative research showed that there are differences in favor of the private school.